ESTUDO DO EFEITO SINÉRGICO ENTRE ÍON METÁLICO E SUBSTÂNCIA BIOATIVA NATURAL - MEIRELES, Jean de Souza; LUZ, Daniele da Silva; VENÂNCIO, Juciely Moreti dos Reis; RODRIGUES, Daniela Cristina Manfroi; DOS ANJOS, Ademir (ANAIS DO ENIC, 2026)
.